Interference‐enhanced Raman scattering in SiO2/Si structures related to reflectance. (13th August 2019) - Vančo, Ľubomír; Kotlár, Mário; Kadlečíková, Magdaléna; Vretenár, Viliam; Vojs, Marian; Kováč, Jaroslav
Abstract: Enhancement of Raman scattering due to optical interference may act as a source of error in the issues necessitating a determination of Raman intensity. Its dependence on thin film thickness is the conventional way how to examine the effects of optical interference in Raman signal. To provide a new platform for evaluation of signal coming from substrate in the presence of a transparent capping, we investigate its relation to reflectance ( R ) instead of the capping thickness. We derived a theoretical model, which was experimentally tested on simple structures consisting of SiO2 deposited on mono‐Si substrates. In agreement between the model and the experiment, interference enhancement is proportional to the product of (1 − R ) terms taken at excitation and scattered light wavenumbers. We experimented with two different Raman bands in Si on two different Raman systems. The model was valid regardless of excitation, Raman band, and grating. Constructed for normal incidence, it was in agreement with experiment using objectives with numerical apertures up to 0.25 (0.32). The model was valid also in ultraviolet region, where imaginary part in refractive index of Si considerably rises. Abstract : Enhancement factor ( EF ) in Si substrate covered by SiO2 depends on reflectance ( R ) of the entire structure. We proposed a model of EF proportional to the product of (1 − R ) terms taken at the wavenumbers of excitation line and studied Raman band. Constant of proportionality can be calculated from refractive indices.